CARDIAC RESYNCHRONIZATION THERAPY AND MYOCARDIAL PERFUSION OF THE LEFT AND RIGHT VENTRICLES - E. N. Ostroumov; E. D. Kotina; V. A. Shmyrov; V. V. Slobodyanik; V. V. Tonkoshkurova; N. P. Mozeiko; I. M. Ilyinski; D. V. Shumakov (Вестник трансплантологии и искусственных органов, 2012)
The decision to install cardiac resynchronization device in patients may be associated not with the apparent clini- cal effectiveness, but for other reasons that require medical consultation. This may be due to the need to create a «bridge» to heart transplantation (HT), for example. In order to predict the outcome of CRT, we observed 54 pa- tients with HF, III–IV functional class NYHA, on the waiting list for HT. Cardiomyopathy was diagnosed in 36 patients, various forms of ischemic heart disease was diagnosed in 17 patients, all with the ECG determined left bundle branch block with QRS complex duration of less than 120 ms. All patients performed gated SPECT before and after CRT with standard methods of research. LVEF at baseline did not exceed 35%. Monitoring was continued for 2 years after the start of the CRT. The results were divided into two groups. Group 1 consisted of patients who need HT for 2 years, in spite of the CRT (11 patients). Group 2 consisted of patients who have an increase in LVEF of at least 10% after CRT (28 patients). When comparing the initial and final performance with the help of the Main- Whitney in both groups, most significant differences were found in the assessment of myocardial perfusion relation- ships lateral walls of LV and RV. The decrease in the ratio between the level of perfusion of the lateral walls of LV and RV < 2,0 reduces the effectiveness of CRT, and within two years, there occured a need for a heart transplant.